Hasil Belajar Peserta Didik Kelas IV SD dengan Menerapkan Model Pembelajaran Round Table - sela hasanah (Universitas Sriwijaya, 2019)
ABSTRACT:The purpose of this study was to improve the learning outcomes of fourth grade students of SD Negeri 40 Palembang in my Subtem and My Goals by Implementing the Round Table Learning Model. This research was conducted in the even semester of the academic year 2019/2020. The research method used is classroom action research (CAR) with 3 cycles of action. The research subjects were students of class IV B, which amounted to 24 students consisting of 12 male students and 12 female students. Data collection techniques used are test and observation. From the results of the study, the activity of students in the first cycle with an average of 65.9 and classified as active. In the second cycle, the results of observations of the activities of students with an average of 73.8 and classified as active. In the third cycle, there was an increase with an average of 81.7 and classified as very active. Learning outcomes of students also experienced an increase in the first cycle there were 15 students who achieved grades more than or equal to 70 with a classical percentage of 62.5%. In the second cycle there was an increase of 18 students who achieved grades more than or equal to 70 with classical completeness of 75%. In cycle III learning completeness increased with 20 students who achieved grades more than or equal to 70 with classical completeness of 83.3%. Thus it can be concluded that the round table learning model can improve the learning outcomes of fourth grade students of SD Negeri 40 Palembang.Keywords: round table learning model, learning outcomes ABSTRAK:Tujuan penelitian ini adalah meningkatkan hasil belajar peserta didik kelas IV SD Negeri 40 Palembang pada Subtema Aku dan Cita-citaku dengan Menerapkan Model Pembelajaran Round Table. Penelitian ini dilaksanakan pada semester genap tahun ajaran 2019/2020. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) dengan 3 siklus tindakan. Subjek penelitian adalah peserta didik kelas IV B, yang berjumlah 24 peserta didik terdiri dari 12 peserta didik laki-laki dan 12 peserta didik perempuan. Teknik pengumpulan data yang digunakan yaitu tes dan observasi. Dari hasil penelitian, aktivitas peserta didik pada siklus I dengan rata-rata 65,9 dan tergolong aktif. Pada siklus II, hasil observasi aktivitas peserta didik dengan rata-rata 73,8 dan tergolong aktif. Pada siklus III, terjadi peningkatan dengan rata-rata 81,7 dan tergolong sangat aktif. Hasil belajar peserta didik juga mengalami peningkatan pada siklus I terdapat 15 peserta didik yang mencapai nilai lebih dari atau sama dengan 70 dengan presentase klasikal 62,5%. Pada siklus II terjadi peningkatan sebanyak 18 peserta didik yang mencapai nilai lebih dari atau sama dengan 70 dengan ketuntasan klasikal sebesar 75%. Pada siklus III ketuntasan belajar meningkat dengan 20 peserta didik yang mencapai nilai lebih dari atau sama dengan 70 dengan ketuntasan klasikal 83,3%. Dengan demikian dapat disimpulkan bahwa model pembelajaran round table dapat meningkatkan hasil belajar peserta didik kelas IV SD Negeri 40 Palembang.Katakunci: model pembelajaran round table, hasil belajar